Inspired by the Bengal Renaissance: Rokeya's role in the education and emancipation of Bengali (Muslim) women - Quayum, Mohammad Abdul (Orient Blackswan, 2016)
The article examines the influences of the Bengal Renaissance on the mind and sensibility of Rokeya Sakhwat Hossain and investigates how she systematically worked for the education of Bengali Muslim women in India to empower them and eventually pave the way for their social and cultural emancipation. The article seeks to locate Rokeya as a pioneering and heroic "feminist" writer before the emergence of feminism as a movement in British South Asia.